Topology optimization design of improved response surface method for time-variant reliability. (August 2020) - Gan, Ning; Wang, Qianxuan
Abstract: This paper proposes an effective and efficient method for topology optimization with a time-variant reliability constraint. A decoupling strategy is used to decompose the time-variant reliability topology optimization into a time-variant analysis and time-invariant deterministic topology optimization, thus improving the efficiency of the optimization calculation. The reliability analysis will use the PHI2 method and an improved response surface method to estimate the time-variant reliability level and satisfy the reliability constraint. Continuously updated design points derived from a time-varying reliability analysis are used for topology optimization using the BESO method. Finally, some numerical examples of the time-variant reliability topology optimization problems are provided to illustrate the efficiency of the proposed method and its ability to determine the optimal solution. Highlights: A decoupling strategy is used to decompose the time-variant reliability topology optimization into time-variant analysis and time-invariant deterministic topology optimization. PHI2 method and improved response surface method are used to estimate the time-variant reliability level. The accuracy of the proposed algorithm is verified with monte carlo simulation.